The fertility response to cutting child related welfare benefits - Malte Sandner; Frederik Wiynck (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2022)
Despite long-term interest whether welfare benefits motivate fertility, evidence from research has not been consistent. This paper contributes new evidence to this debate by investigating the fertility effect of a German welfare reform. The reform decreased the household income of families on welfare by 18 percent in the first year after the birth of a baby. Using exclusive German social security data on over 460,000 affected women, our analysis finds the reform leads to a fertility reduction of 6.8 percent. This result implies that for mothers on welfare, fertility has an income elasticity of 0.38, which is much smaller than that of general populations reported in the literature. Our findings suggest that welfare recipients' fertility reacts less strongly to financial incentives than the fertility of overall populations. – – Bereits seit langer Zeit wird untersucht, ob Sozialleistungen die Fertilität anregen. Dennoch ist die Forschung bisher nicht konsistent. Dieses Papier trägt zu ebendieser Debatte bei, indem es den Fertilitätseffekt einer deutschen Sozialleistungsreform untersucht. Die Reform verringerte das Haushaltseinkommen von Familien mit Sozialhilfebezug um 18 Prozent im ersten Jahr nach Geburt ihres Kindes. Die Analyse exklusiver Sozialversicherungsdaten von über 460.000 betroffenen Frauen ergibt, dass die Reform zu einer Verringerung der Fertilität von 6,8 Prozent führt. Dieses Ergebnis legt nahe, dass für sozialhilfebeziehende Mütter Fertilität eine Einkommenselastizität von 0,38 hat. Das ist wesentlich kleiner als in bisherigen Untersuchungen zur Gesamtbevölkerung angenommen. Unsere Befunden lassen darauf schließen, dass die Fertilität von Sozialhilfeempfängern weniger stark auf finanzielle Anreize reagiert, als die der Gesamtbevölkerung.
Keywords: J13; I38; C54; 330; Fertility; parental leave benefits; welfare benefits